Implications of technical-instrumental rationality in health education: pending challenges (2017)
The current era, characterized by postmodernism, puts a strain on the true meaning of higher education, specifically in relation to health, which has been guided by logics binding the technical, reflective and critical rationality of those who train professionals. One of the core concepts of this contemporary debate is the imposition of technical-instrumental rationality as the only paradigm of knowledge. This imposition eclipses the epistemological foundation of educational work and the teleological problems of every teaching act (1). Actually, in the words of Heidegger, insofar as man technically constructs the world as an object, the path to the open is voluntarily and completely obstructed. (2, p218). In this context, it is possible to observe the technical-instrumental rationality of knowledge, which constitutes one of the cognitive interests that underlies all human practices and, specifically, the teaching methods in health.